The BECCS Implementation Gap–A Swedish Case Study - Fuss, Sabine; Johnsson, Filip (Frontiers in Energy Research, 2021)
The IPCC has assessed a variety of pathways that could still lead to achievement of the ambitious climate targets set in the Paris Agreement. However, the longer time that climate action is delayed, the more the achievement of this goal will depend on Carbon Dioxide Removal (CDR) technologies and practices. In the models behind these pathways, the main CDR technology is Bioenergy combined with Carbon Capture and Storage (BECCS). We review the role that BECCS could play in reaching net-zero targets based on the existing 1.5°C scenarios. Such scenarios presented in the literature typically have BECCS at a GtCO2 per year scale. We also assess the potentials and obstacles for BECCS implementation at the national level, applying Sweden as a case study. Given that BECCS deployment has scarcely started and, thus, is far from capturing 1 GtCO2 per year, with lead times on the scale of multiple years, we conclude that there will be a large implementation gap unless BECCS development is immediately intensified, emissions are reduced at a much faster pace or removals realized through other CDR measures. In the national case study, we show that Sweden has favorable conditions for BECCS in that it has large point sources of biogenic emissions, and that BECCS has been identified as one potential “supplementary measure” for reaching the Swedish target of net-zero emissions in 2045. Yet, work on planning for BECCS implementation has started only recently and would need to be accelerated to close the implementation gap between the present advancement and the targets for BECCS proposed in a recent public inquiry on the roles of supplementary measures. An assessment of two ramp-up scenarios for BECCS demonstrates that it should in principle be possible to reach the currently envisaged deployment scales, but this will require prompt introduction of political and economic incentives. The main barriers are thus not due to technological immaturity, but are rather of a socio-economic, political and institutional nature.